False Memories: theoretical and methodological issues - Alves, Cíntia Marques; Lopes, Ederaldo José (Paidéia (Ribeirão Preto), 2007)
False memories (FM´s) occur when a person remembers events that never happened to him, situations at which he/she was not present, places where he/she has never been, or when he/she remembers some event differently from what really happened. The purpose of this work was to present a historical review of FM´s, some theoretical models and their contributions to the comprehension about them. The DRM (Deese-Roediger-McDemott), which is used to study FM´s, is also presented. We could see the importance and the necessity of this study for Psychology and for psychologists, mainly those who work directly with the people's memory.